Dynamics of the Indonesian Parliament in Formulating Food Laws to Achieve Food Security at the End of the New Order - Pramestuti, Agustina Wilujeng; Rochwulaningsih, Yety; Sulistiyono, Singgih Tri (Indonesian Historical Studies, 2023)
The Indonesian draft law on food explicitly recognizes food as a basic human need and a fundamental right for every citizen. Staple foods are also commodities that significantly influence the nation's economic life. Therefore, food issues in Indonesia have always been a government concern. In the early days of independence, Indonesia faced the threat of a food crisis. This ongoing threat has consistently garnered attention from both the executive and legislative branches throughout various eras. Using a historical method, this article outlines the dynamics of the Indonesian parliament during the New Order era in formulating food laws. The urgency of these laws lies in regulating food production and distribution to ensure the fulfillment of the Indonesian people's food needs. Furthermore, government policies should ideally be oriented towards food sovereignty. Research findings reveal that the Food Law formulated and passed at the end of the New Order era actually attempted to be oriented towards food security and was critical of capitalism. This can be seen from the opinions of the factions in parliament during the formulation of the Food Law.